Graft Failure in Patients With Hematological Malignancies: A Successful Salvage With a Second Transplantation From a Different Haploidentical Donor - Sun, Yu-Qian; Wang, Yu; Wang, Feng-Rong; Yan, Chen-Hua; Cheng, Yi-Fei; Chen, Yu-Hong; Zhang, Yuan-Yuan; Han, Ting-Ting; Han, Wei; Suo, Pan; Xu, Lan-Ping; Zhang, Xiao-Hui; et al. (Frontiers in Medicine, 2021)
Graft failure (GF) is a fatal complication of allogeneic stem cell transplantation, especially after haploidentical transplantation. A second transplantation is usually necessary to save the patient’s life. However, there is no standardized regimen, and the outcome is usually disappointing. We report on a prospective single-center study using a reduced-intensity conditioning regimen with different haploidentical donors (HIDs). Patients with GF after the first transplantation were enrolled in a prospective single-arm clinical trial (ClinicalTrials.Gov ID: NCT03717545) at the Peking University Institute of Hematology. The conditioning regimen consisted of fludarabine (30 mg/m2) (days -6 to -2) and cyclophosphamide (1000 mg/m2/day) (days -5 to -4). Patients underwent a second transplant from a different HID using a granulocyte colony-stimulating factor primed bone marrow and peripheral blood stem cells. The primary outcome was neutrophil engraftment at day 28. The secondary outcomes included platelet engraftment at day 100, transplant-related mortality (TRM) at day 30, TRM at day 100, and overall survival (OS) at day 100. From March 2018 to June 2020, 13 patients were enrolled in this clinical trial. As for the first transplantation, 11 patients underwent haploidentical transplantations and 2 underwent unrelated donor transplantations. At the time of GF, 3 patients had complete donor chimerism, 5 had mixed chimerism, and 5 had complete recipient chimerism. The median time from the first transplantation to the second transplantation was 49 (range 35-120) days. The medians of infused cell doses were as follows: mononuclear cells 7.93 (5.95-12.51) ×108/kg and CD34 + cells 2.28 (0.75-5.57) ×106/kg. All 13 patients achieved neutrophil engraftment after the second transplantation, with a median engraftment time of 11 (range 10-20) days after transplantation. The platelet engraftment rate on day 100 after transplantation was 76.9%. The TRMs at day 28, day 100, and 1-year were 0%, 0%, and 23.1%, respectively. The OS and disease-free survival at 1-year were 56.6% and 48.4%, respectively. For patients with GF after first transplantation, a second transplantation using a fludarabine/ cyclophosphamide regimen from a different HID was a promising salvage option. Further investigation is needed to confirm the suitability of this method.